The Morphological Features and Mitochondrial Oxidative Stress Mechanism of the Retinal Neurons Apoptosis in Early Diabetic Rats. (2nd January 2014) - Li, Xiaoyan; Zhang, Maonian; Zhou, Huanfen
Abstract : This paper aims to explore the relationship of retinal neuron apoptosis and manganese superoxidase dismutase (MnSOD) at early phase of diabetic retinopathy. Sprague-Dawley rats were grouped into normal controls and diabetics. Data were collected after 4, 8, and 12 weeks (n = 12 ). The pathological changes and ultrastructure of the retina, the apoptosis rate of retinal neurons by TdT-mediated dUTP nick end label (TUNEL), mRNA expressions of MnSOD and copper-zinc superoxide dismutase (Cu–Zn SOD), and the activities of total SOD (T-SOD) and subtypes of SOD were tested. For the controls, there was no abnormal structure or apoptosis of retinal neurons at any time. There was no change of structure for rats with diabetes at 4 or 8 weeks, but there was a decrease of retinal ganglion cells (RGCs) number and thinner inner nuclear layer (INL) at 12 weeks. The apoptosis ratio of RGCs was higher than that of the controls at 8 and 12 weeks (P < 0.001 ). The activity and mRNA levels of MnSOD were lower in diabetics at 4, 8, and 12 weeks (P < 0.05 ). In summary, the apoptosis of the retinal neurons occurred at 8 weeks after the onset of diabetes. Retinal neuron apoptosis in early diabetic rats may be associated with the decreased activity and mRNA of MnSOD.